Optimal locations of U.S. fast charging stations for long-distance trip completion by battery electric vehicles. (20th March 2019) - He, Yawei; Kockelman, Kara M.; Perrine, Kenneth A.
Abstract: Due to environmental and energy challenges, promoting battery electric vehicles (BEVs) is a popular policy for many countries. However, a lack of fast recharging infrastructure and limitations on BEV range limit their purchase and use. It is important to have a well-designed charging station network, so this paper uses U.S. long-distance travel data to place charging stations with the objective of maximizing long-distance trip completions. Each scenario assumes a certain number of charging stations—from 50 to 250, across the U.S., and an all-electric-range (AER) of 60–250 miles (97–402 km). The problem is formulated as a mixed integer program, and a modified flow-refueling location model (FRLM) is solved via a branch-and-bound algorithm. Results reveal that the 60-mile-AER percentage varies between 31% and 65%, as one increases station count from 50 stations to 250 stations. At least 100 mile-range (161 km) BEVs appear needed, to avoid long-distance-trip issues for the great majority of U.S. households. This research also provides an effective method to decide the number and locations of fast charging stations for different conditions, to enable better planning and more sustainable transportation systems. Highlights: Battery electric vehicles (BEVs) are range-limited and can require long charge times. Here, various BEV ranges and charging station counts are analyzed for the U.S. network. Charging stations sited to maximize completion of U.S. long-distance person-trips. 200-mile-range BEVs can serve nearly all U.S. long-distance trips with just 100 charging locations. Key locations for long-distance trip completion are in the eastern and central U.S.